2021
DOI: 10.1111/jcal.12527
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐persistence and difficulty in a game‐based learning environment for computational thinking acquisition

Abstract: Persistence has been identified as a crucial quality of learning. However, it is hard to attain in online game‐based environments as the drive to progress in the game may influence the ability to achieve the learning goals. This study aimed to examine the associations between micro‐persistence, that is, the tendency to complete an individual task successfully, and task difficulty while acquiring computational thinking (CT). We further explored whether contextual or personal attributes better explain micro‐pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Naturally, they wake up so late in the morning that they do not even have time to eat breakfast. Hence, the person looks sluggish, confused, and has no interest in doing anything [ 18 ]. If we do not even have the passion to study and live, can we still study efficiently?…”
Section: Strategies and Suggestions For College Students To Study Hap...mentioning
confidence: 99%
“…Naturally, they wake up so late in the morning that they do not even have time to eat breakfast. Hence, the person looks sluggish, confused, and has no interest in doing anything [ 18 ]. If we do not even have the passion to study and live, can we still study efficiently?…”
Section: Strategies and Suggestions For College Students To Study Hap...mentioning
confidence: 99%
“…Taken together, we found that regarding achievements, the halt-and-re-run persistence mechanism (portrayed by Some Incomplete and Single Complete, Multiple Incomplete and No Complete) is productive overall, while the complete-and-rerun persistence mechanism (portrayed by Multiple Complete and No Incomplete) is potentially counterproductive. This is an important addition to the existing literature, which recently suggested that micro-persistence showed a somewhat positive contribution to learning (Fang et al, 2017;Israel-Fishelson & Hershkovitz, 2021;Auvinen et al, 2015;Delen & Liew, 2016;Kovanović et al, 2016;Motz et al, 2019;Nguyen, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…Self-efficacy, satisfaction and IM are variables which lead to student persistence [44]. In addition, micropersistence is the aspiration to complete an individual task successfully, e.g., in game-based learning environments, and can improve CT acquisition and the learning processes involved and has been recognized as a promising approach to improve learning outcomes [43], [45], [46]. Thus, behavior in the response of a given challenge according to the characteristics of the players could provide clues about their abilities and interests, and even predict their school achievement [39].…”
Section: B Intrinsic Motivation In Game-based Environmentsmentioning
confidence: 99%
“…• Persistence: is a valuable skill when solving problems and can improve CT acquisition and the learning processes involved [45], [54]. It can be defined as the will to complete a learning process and achieve the learning goals.…”
Section: B Research Variables and Data Collectedmentioning
confidence: 99%